1993
DOI: 10.1159/000216892
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Study in Patients Who Had Undergone Surgery for Meningioma

Abstract: Abnormal fibrinolysis and thrombotic complications have been often observed in patients who had undergone surgery for meningioma. Fourteen patients, affected by meningioma, were studied before surgery, during surgery and 24 h after surgery in order to evaluate the modifications of the fibrinolysis system and the coagulation physiological inhibitors. Before surgery, no patient showed hyperfibrinolysis and/or modifications of coagulation physiological inhibitors. During surgery, an activation of fibrinolysis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Other authors have reported similar findings in adults as well as in children [23][24][25]. This fibrinolysis syndrome noted by so many authors, and with a reported incidence of 64% by Dragoni et al [26], was not evident in our TEG results of up to 1 h long analysis.…”
Section: Discussionsupporting
confidence: 82%
“…Other authors have reported similar findings in adults as well as in children [23][24][25]. This fibrinolysis syndrome noted by so many authors, and with a reported incidence of 64% by Dragoni et al [26], was not evident in our TEG results of up to 1 h long analysis.…”
Section: Discussionsupporting
confidence: 82%
“…21 Brain tumor surgery, in particular meningioma resection, is associated with activation of the fibrinolytic system. 22 The third important finding is the large percentage of patients who receive transfusions of blood products intraoperatively or immediately after surgery. Along with orthopedic procedures, neurosurgical interventions are the most common cause for perioperative blood transfusion in children.…”
Section: Discussionmentioning
confidence: 99%